Israel after the Exile : sixth and fifth centuries, B.C. - Lofthouse, W.F., (William Frederick) 1871- (Oxford, UK : The Clarendon Press, 1928)
new
Includes index.
Keywords: Bible. -- history of contemporary events; Israel -- second temple period; Palestine -- antiquities